Trypanosoma evansi: Cloning and expression in Spodoptera fugiperda insect cells of the diagnostic antigen RoTat1.2 - Urakawa, T.; Verloo, D.; Moens, L.; Büscher, Philippe; Majiwa, Phelix A.O. (Elsevier, 2001)
A complementary DNA encoding the variant surface glycoprotein (VSG) of Trypanosoma evansi Rode Trypanozoon antigenic type (RoTat)1.2, currently used for experimental serological diagnosis of T. evansi infection in livestock, was cloned as a recombinant plasmid and sequenced. A recombinant baculovirus containing the coding region of RoTat1.2 VSG was constructed to express the protein in Spodoptera fugiperda insect cells. From this, sufficient quantities of the recombinant protein are being produced for empirical and wide-scale objective assessment of the diagnostic potential of this antigen. The gene encoding the RoTat1.2 VSG was shown by PCR to be present in the genomes of many different cloned isolates of T. evansi, but not T. brucei, from geographically separate regions of Africa, Asia, and South America. With the recombinant RoTat1.2 at hand, it is now possible to investigate the extent to which epitopes on this VSG are conserved among different T. evansi isolates.